Research progress on moyamoya disease combined with thyroid diseases - Zhang, Guibo; Liu, Erheng; Tan, XueYi; Liu, Chengyuan; Yang, Shuaifeng (Frontiers in Endocrinology, 2023)
Moyamoya disease (MMD), also known as abnormal cerebral vascular network disease, is characterized by progressive occlusion or stenosis of the internal carotid and cerebral arteries, as well as the formation of an abnormal cerebral vascular network. It can occur anywhere in the world but is most common in China, Japan, and the Republic of Korea. In recent years, there have been increasing reports on the coexistence of thyroid diseases and MMD, but the mechanism of their coexistence is still unclear. For this article, we used keywords such as “moyamoya disease”, “thyroid”, “Grave disease”, “thyrotoxicosis”, and “thyroid autoimmune antibodies” to search for 52 articles that met the requirements in medical databases such as PubMed and Web of Science. This article also reviews the research on the role of thyroid hormone, the mechanism of immune antibodies, the possible correlation between thyroid diseases and MMD disease genes, and the treatment methods, and discusses the possible relationship between MMD and thyroid diseases to provide a reference for the pathogenesis and treatment of MMD with thyroid diseases.